Enhancing Students’ Speaking Skills through Classroom Action Research in EFL Classrooms - Eka Pujiastuti; Hera Hartati; Saifudin; Zuhrotun Nisa (Foreign Language Instruction Probe, 2026)
This study addresses the persistent issue of limited speaking performance among EFL students, particularly in terms of fluency, accuracy, pronunciation, and confidence, which hinders effective classroom communication. Previous studies have highlighted similar challenges; however, empirical evidence on the systematic use of iterative teaching practices to improve multiple dimensions of speaking skills remains limited. Therefore, this study aims to investigate how Classroom Action Research (CAR) can enhance students’ speaking skills in an authentic EFL context. This research employed a qualitative CAR design conducted at Politeknik Mitra Karya Mandiri Ketanggungan Brebes, involving 25 students. The study was implemented in three cycles, consisting of planning, acting, observing, and reflecting stages. Data were collected through classroom observation, interviews, and documentation, and analyzed using qualitative techniques, including data reduction, data display, and conclusion drawing. The findings reveal a consistent improvement in students’ speaking skills across all indicators, supported by both qualitative observations and quantitative score increases. The study highlights the effectiveness of reflective and cyclical teaching practices in improving speaking performance. It is recommended that future research adopt mixed-method approaches and explore the integration of innovative instructional strategies to further enhance EFL speaking instruction.